Could consumption of yam (Dioscorea) or its extract be beneficial in controlling glycaemia: a systematic review. Issue 4 (28th August 2022) - Alharazi, Waad Z.; McGowen, Anthony; Rose, Peter; Jethwa, Preeti H.
Abstract: Yam ( Dioscorea spp. ) and its associated extracts have been shown to possess a variety of biological activities and identified as beneficial in the control of glycaemia in patients with type II diabetes mellitus (T2DM). The objective was to conduct a systematic search of the literature to investigate whether yam and its extract can improve glycaemia and whether the consumption of yam could be beneficial for managing T2DM. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and the Population, Invention, Comparison and Outcome framework, three databases (PubMed, Scopus and Web of Science) were searched using a key term strategy. Strict inclusion criteria were employed to identify all relevant and available studies. The quality of these studies was assessed using SYRCLE's Risk of Bias tool. Ten studies were included, and all studies consisted of findings from rodent models of diabetes, including animals consuming high fat diets or genetic models of diabetes. All ten studies showed that the consumption of yam and/or its extracts (containing dioscin, dioscorin, diosgenin, DA-9801/02 or Chinese yam polysaccharides) improved glycaemia. These included improvements in fasting blood glucose and reductions in glucose and increase in insulin levels following a glucose tolerance test. Furthermore, significant changes in body weight and adiposity were observed in nine studies, these included improvements in lipid biomarkers in four and reductions in inflammatory markers in one. The current work indicates that the consumption of yam or its extracts can be beneficial for improving blood glucose; however, the molecular mechanism for these effects remains largely unknown. Future trials on human subjects are warranted.